Percutaneous fetoscopic spina bifida repair: effect on ambulation and need for postnatal cerebrospinal fluid diversion and bladder catheterization. (13th September 2021) - Lapa, D. A.; Chmait, R. H.; Gielchinsky, Y.; Yamamoto, M.; Persico, N.; Santorum, M.; Gil, M. M.; Trigo, L.; Quintero, R. A.; Nicolaides, K. H.
Abstract: Objective: A trial comparing prenatal with postnatal open spina bifida (OSB) repair established that prenatal surgery was associated with better postnatal outcome. However, in the trial, fetal surgery was carried out through hysterotomy. Minimally invasive approaches are being developed to mitigate the risks of open maternal–fetal surgery. The objective of this study was to investigate the impact of a novel neurosurgical technique for percutaneous fetoscopic repair of fetal OSB, the skin‐over‐biocellulose for antenatal fetoscopic repair (SAFER) technique, on long‐term postnatal outcome. Methods: This study examined descriptive data for all patients undergoing fetoscopic OSB repair who had available 12‐ and 30‐month follow‐up data for assessment of need for cerebrospinal fluid (CSF) diversion and need for bladder catheterization and ambulation, respectively, from eight centers that perform prenatal OSB repair via percutaneous fetoscopy using a biocellulose patch between the neural placode and skin/myofascial flap, without suture of the dura mater (SAFER technique). Univariate and multivariate logistic regression analyses were used to examine the effect of different factors on need for CSF diversion at 12 months and ambulation and need for bladder catheterization at 30 months. Potential cofactors included gestational age at fetal surgery and delivery, preoperative ultrasound findings of anatomical level of the lesion, cerebral lateral ventricular diameter, lesion type and presence of bilateral talipes, as well as postnatal findings of CSF leakage at birth, motor level, presence of bilateral talipes and reversal of hindbrain herniation. Results: A total of 170 consecutive patients with fetal OSB were treated prenatally using the SAFER technique. Among these, 103 babies had follow‐up at 12 months of age and 59 had follow‐up at 30 months of age. At 12 months of age, 53.4% (55/103) of babies did not require ventriculoperitoneal shunt or third ventriculostomy. At 30 months of age, 54.2% (32/59) of children were ambulating independently and 61.0% (36/59) did not require chronic intermittent catheterization of the bladder. Multivariate logistic regression analysis demonstrated that significant prediction of need for CSF diversion was provided by lateral ventricular size and type of lesion (myeloschisis). Significant predictors of ambulatory status were prenatal bilateral talipes and anatomical and functional motor levels of the lesion. There were no significant predictors of need for bladder catheterization. Conclusion: Children who underwent prenatal OSB repair via the percutaneous fetoscopic SAFER technique achieved long‐term neurological outcomes similar to those reported in the literature after hysterotomy‐assisted OSB repair. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. Linked article: There is a comment on this article by Macedo Jr and Leal da Cruz. Click here to view the Correspondence. RESUMEN: Reparación percutánea fetoscópica de la espina bífida: efecto sobre la deambulación y la necesidad de derivación de líquido cefalorraquídeo y cateterización vesical postnatales Objetivo: En un ensayo para comparar la reparación prenatal con la postnatal de la espina bífida abierta (EBA) se estableció que la cirugía prenatal estaba asociada con un mejor resultado postnatal. Sin embargo, en dicho ensayo, la cirugía fetal se llevó a cabo mediante histerotomía. Se están desarrollando métodos mínimamente invasivos para mitigar los riesgos de la cirugía abierta materno‐fetal. El objetivo de este estudio fue investigar el impacto en el resultado postnatal a largo plazo de una técnica neuroquirúrgica novedosa para la reparación fetoscópica percutánea de la EBA fetal, como es la técnica de piel sobre biocelulosa para la reparación fetoscópica prenatal (SAFER, por sus siglas en inglés). Métodos: Este estudio analizó datos descriptivos de todos los pacientes sometidos a reparación fetoscópica de la EBA de los que se disponía de datos de seguimiento a los 12 y 30 meses para evaluar la necesidad de desviación del líquido cefalorraquídeo (LCR) y la necesidad de cateterización vesical y deambulación, respectivamente, los cuales procedían de ocho centros que realizan la reparación prenatal de la EBA mediante fetoscopia percutánea utilizando un parche de biocelulosa entre la placoda neural y el colgajo cutáneo/miofascial, sin sutura de la duramadre (técnica SAFER). Se utilizaron análisis de regresión logística univariantes y multivariantes para examinar el efecto de los distintos factores sobre la necesidad de derivación del LCR a los 12 meses y la deambulación y la necesidad de cateterización vesical a los 30 meses. Entre los posibles cofactores estaban la edad gestacional en el momento de la cirugía fetal y del parto, los resultados de ecografías preoperatorias del nivel anatómico de la lesión, el diámetro del ventrículo lateral cerebral, el tipo de lesión y la presencia de pie equinovaro, así como los hallazgos postnatales de pérdida de LCR en el momento del nacimiento, el nivel de motricidad, la presencia de pie equinovaro y la reversión de la hernia del rombencéfalo. Resultados: Se trató prenatalmente un total de 170 pacientes consecutivos con EBA fetal mediante la técnica SAFER. Se dio seguimiento a 103 de los bebés a los 12 meses de edad y a 59 a los 30 meses de edad. A los 12 meses de edad, el 53, 4% (55/103) de los bebés no necesitaron una derivación ventriculoperitoneal o una tercera ventriculostomía. A los 30 meses de edad, el 54, 2% (32/59) de los niños o niñas deambulaban de forma independiente y el 61, 0% (36/59) no necesitaban cateterización vesical intermitente crónica. El análisis de regresión logística multivariante demostró que el tamaño del ventrículo lateral y el tipo de lesión (mielosquisis) proporcionaban una predicción significativa de la necesidad de desviación del LCR. Los parámetros indicativos significativos del estado deambulatorio fueron el pie equinovaro prenatal y los niveles motrices anatómicos y funcionales de la lesión. No hubo parámetros indicativos significativos de la necesidad de cateterización vesical. Conclusión: Los niños que se sometieron a una reparación prenatal de la EBA mediante la técnica percutánea fetoscópica SAFER obtuvieron resultados neurológicos a largo plazo similares a los descritos en la literatura tras una reparación de la EBA mediante histerotomía. © 2021 Los autores. Ultrasound in Obstetrics & Gynecology, publicada por John Wiley & Sons Ltd en nombre de la Sociedad Internacional de Ecografía en Obstetricia y Ginecología. 摘要: 经皮穿刺胎儿镜脊柱裂修复术:对步行的影响以及产后脑脊液分流和膀胱导尿的需要 目的: 一项对比产前和产后开放性脊柱裂(OSB)修复术的试验，证实了产前手术与更好的产后预后有关。但在试验中，胎儿手术是通过剖宫产进行的。正在研制微创方式来缓解开放性产妇‐胎儿手术的风险。本研究目的在于调查一种用于胎儿OSB的经皮穿刺胎儿镜修复的新型神经外科技术(皮肤覆盖生物纤维的产前胎儿镜修复技术(SAFER))对长期产后预后的影响。 方法: 本研究调查了所有进行过胎儿镜OSB修复术的患者的描述性数据，这些患者有12至30个月的随访数据可用于分别评估脑脊液(CSF)分流和膀胱导尿的需要以及对步行的影响。这些患者所来自的八个中心进行了经皮穿刺胎儿镜产前OSB修复术，即在神经基板和皮肤/肌筋膜瓣之间使用一片生物纤维，而无需缝合硬脑膜(即SAFER技术)。使用了单因素和多元逻辑斯蒂回归分析法，针对第12个月CSF分流的需要、步行和在第30个月膀胱导尿的需要，研究了各种不同因素的影响。潜在辅因子有胎儿手术时及分娩时的胎龄、损害在结构上术前超声检查的结果、侧脑室内径、损害类型和双侧畸形足，以及出生时CSF渗漏的产后调查结果、行动水平、双侧畸形足的存在和后脑疝逆转。 结果: 总共连续有170名有胎儿OSB的患者，在产前以SAFER技术进行了治疗。在这些患者中，有103个婴儿在12个月大时进行了随访，还有59个婴儿在30个月大时进行了随访。在12个月大时，53.4%(55/103)的婴儿无需脑室腹膜分流术或第三脑室底造瘘术。在30个月大时，54.2%(32/59)的儿童能独立步行，而且61.0%(36/59)无需长期间歇性膀胱导尿。多元逻辑斯蒂回归分析法证实，对CSF分流需要的预测主要是由侧脑室大小及损害类型(脊髓裂)提供的。步行状态的主要预测因素是产前双侧畸形足以及损害在结构和功能上的运动水平。对于膀胱导尿则无重大预测因素。 结论: 采用经皮穿刺胎儿镜SAFER技术进行产前脊柱裂修复术的儿童，所获得的长期神经学预后类似于文献中所报告的经剖宫产辅助进行OSB修复术的预后。©2020作者。John Wiley&Sons Ltd代表国际妇产科超声学会发表在《妇产科超声》上。